Exploring modes of lecturing as a teaching method in higher education: Student attendance, preference and motivation - Vlachopoulos, Panos; Jan, Shazia (Journal of University Teaching and Learning Practice, 2020)
This paper presents the findings of a large-scale study conducted at an Australian metropolitan university, which seeks to compare attendance in different modes of lecture delivery and student preference and motivation for attendance. The research design collected data for three different teaching methods - on-campus lectures, live streaming utility and lecture recordings via lecture capture. The study addresses the broader question of the value students place on the modes of lecturing, as indicated by their attendance patterns, usage of lecture recordings, and preferences and motivations for the same. Overall, the study confirms the student preference for flexibility when accessing or attending lectures, with those choosing both on-campus and live streaming lecture delivery, also having a strong preference for using recorded lectures. Implications of findings of the study which was conducted pre-COVID-19 extend to a post-coronavirus world as well with implications for infrastructure and resource planning for universities with changing student demographics and flexibility requirements and challenges brought on by a global health and economic crises.